Disaster induced Migration and Social Conflict: An Enquiry in the Light of Cyclone Sidr in Bangladesh - Ahmed, Bashir; Islam, Mohammad Tarikul; Hasan, A.S.M. Firoz-UL (Economic Journal of Nepal, 2014)
Conflict induced internal displacement has been a burning problem worldwide as a result of increasing disaster due to clime change. Disaster induced migration has the potential to become a phenomenon of a scale and scope not experienced in human memory. Displacement due to disaster is considered to be a socio-economic and political problem, when it gets solved, the issue of displacement is also ignored. Bangladesh was struck by a category-4 cyclone (Sidr) on the evening of 15 November in 2007 which resulted in displacement of 650,000 people. Such migration posed a serious threat towards social stability and leads towards social conflict. Migration is generally considered as a source of social conflict. Over 3 million people live in slums and squatters of Dhaka city with very little utility service. Slums and squatters are the informal settlements of Dhaka city that accommodate the low-income group of people. Conflict (quarrel, clash, fight) in the slums and squatters is a regular phenomenon. The displaced persons are knowingly and unknowingly discriminated on various grounds and suffer as the survivors of various stigmas. The study reveals that, undue influence by the muscleman, discrimination between migrated and poor slum dwellers, and demand for money by the terrorist group, ignorance to the migrated people by the different quarters and sexual harassment to the migrated adolescent girls are responsible for slumping of social conflict. Their voices are ignored; theirple as are neglected and thus they are excluded from the mainstreamed section in the society.